Cannabinoids: Friend or foe?. Issue 6 (June 2015) - Le Foll, B; Tyndale, RF
<x xml:space="preserve">Abstract</x> This issue of Clinical Pharmacology & Therapeutics focuses on cannabinoids. Our understanding of these interesting endogenous and synthetic compounds, and their role in the cannabinoid system, has evolved dramatically, in part because of the acquisition of new research tools. Cannabis has been used for centuries by humans for recreational and medicinal purposes, however, there is substantial evidence that cannabis use can expose people to varying complications (e.g., risk of addiction, cognitive impairment), thus, it is important to determine the benefit/risk of cannabis with precision and to implement policy measures based on evidence to maximize the benefits and minimize the harm. Novel cannabinoid drugs are emerging for medicinal use (e.g., dronabinol, nabiximols) and as illicit drugs (e.g., Spice, K2) perpetuating the perception that cannabinoid drugs can be a friend or foe. This special issue will cover these various aspects of cannabinoid pharmacology and therapeutics ranging from basic chemistry, pharmacokinetics, pharmacodynamics, and clinical trial results, to policy and education efforts in this area.